2015
DOI: 10.1038/ijo.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cue-induced firing of ventral tegmental area dopamine neurons by leptin and ghrelin

Abstract: Background/objectives:The rewarding value of palatable foods contributes to overconsumption, even in satiated subjects. Midbrain dopaminergic activity in response to reward-predicting environmental stimuli drives reward-seeking and motivated behavior for food rewards. This mesolimbic dopamine (DA) system is sensitive to changes in energy balance, yet it has thus far not been established whether reward signaling of DA neurons in vivo is under control of hormones that signal appetite and energy balance such as g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 49 publications
0
40
0
1
Order By: Relevance
“…S4E). Together, these data provide evidence that enhanced LHA Nts neuronal activity counteracts the drive to consume palatable food in an energy-restricted state, similar to what occurs after diet-induced weight loss (Sumithran et al, 2011; van der Plasse et al, 2015). …”
Section: Resultsmentioning
confidence: 55%
“…S4E). Together, these data provide evidence that enhanced LHA Nts neuronal activity counteracts the drive to consume palatable food in an energy-restricted state, similar to what occurs after diet-induced weight loss (Sumithran et al, 2011; van der Plasse et al, 2015). …”
Section: Resultsmentioning
confidence: 55%
“…Given that insulin also acts in the hypothalamus to promote satiety [38], this suggests a potential mechanism by which diet may influence circuits important for reward learning and homeostasis. Indeed, a number of nutritionally-regulated hormones involved in hypothalamic control of feeding and glucose homeostasis—including glucagon-like peptide 1 [39], amylin [40], leptin [41], and ghrelin [42]—also modulate mesocorticolimbic dopamine signaling. Accordingly, recent data suggest that hypothalamic feeding circuits are regulated by sensory input [9], and may integrate information from reward circuits about nutritional and hedonic properties of food to direct metabolic learning and memory [43].…”
Section: Metabolic Control Of Food Cue Reactivity In the Nucleus Accumentioning
confidence: 99%
“…Furthermore, both dopaminergic as well as opioid signaling, which are crucial during the processing of the anticipation or receipt of rewards, respectively (23), have been found to be affected by homeostatic satiety signaling (5,(24)(25)(26). However, studies investigating neural reactivity to food stimuli found both baseline as well as reward-level-dependent homeostasis-induced increases in dopamine (27)(28)(29) and opioid signaling (30,31). Therefore, it still remains unclear whether mesolimbic reward signaling during a fasted state is generally increased irrespective of reward modality or if it is only increased for food reward.…”
mentioning
confidence: 96%